Impact of Demographic Variables on Stress Level among Regional Transport Office Employees (International Journal of Food and Nutritional Sciences, 2022)
The word ‘‘stress’’ may have originated from the Latin word stringere meaning todraw tight Cox, T. (1978). Since the seventeenth century, the term "stress" has been used todescribe difficulty (Hinkle, L.E., 1973)